Financial Integration and Variance Decomposition of Asian Stock Market: Evidence from India - Nikhil Bhardwaj; Nishi Sharma; Anupreet Kaur Mavi (Asian Journal of Business and Accounting, 2023)
Manuscript type: Research paper Research aims: International investments made in non-integrated economies provide benefits of portfolio diversification, but investment made in integrated economies may lead to oscillations due to volatility spillover. Therefore, the knowledge of market linkage of an economy is imperative for investors, as well as regulators. In this context, the present paper investigates the financial integration of the Indian stock market with China, Hong Kong, Japan, UK and USA. Design/Methodology/Approach: To examine the financial integration in the long run, closing daily indices of leading stock markets of respective countries have been analysed through the Johansen cointegration method over a period of 20 years from 2002 to 2022. The vector error correction model has been applied to examine whether market equilibrium can be restored after an infusion of shock. The short run linkage has been investigated through a causality test. Further the possibility of volatility spillover has been examined through variance decomposition and impulse response function. Research findings: The results show cointegration among the selected markets, which indicates the possibility of convergence towards market equilibrium in the long run. The stock markets of India and USA were observed to have a bidirectional causal relationship indicating lesser chances of benefits from international portfolio diversification. The results reveal the sensitivity of the Indian stock market to innovations in the UK and USA. However, no significant influence of the Hong Kong, Japanese, and Chinese stock markets has been observed on the Indian stock market. Further, the Indian stock market has a significant contribution to the volatility of other stock markets, except the Chinese stock market. Theoretical contribution/Originality: The present study is crucial owing to two prominent reasons. Firstly, the linkage between various financial markets is very dynamic and needs to be studied in the present context. Secondly, the linkage of Indian economy with other countries has increased manifolds in recent few years so it will be fruitful to analyse the linkage of Indian economy with other economies. Practitioner/Policy implications: The findings are useful to investors while designing international portfolios to reap diversification benefits. The results are fruitful for market regulatory bodies to mitigate the adverse impact of volatility spillover. Research limitation/Implications: The study can be extended to other markets, monthly data and different sub-periods